Nach der Kulturgeschichte Perspektiven einer neuen Ideen- und Sozialgeschichte der deutschen Literatur - Benz, Maximilian; Stiening, Gideon (De Gruyter, 2021)
The predicted end of the era of cultural studies in the humanities and social sciences opens the possibility for serious methodological debate. The volume collects essays by medievalists and modern linguists that explore conceptual and social historical perspectives on the period from the 12th to the 21st centuries, developing a balance between ideas and realities as respectively different but mutually resonating contexts.